Impact of Padma Multi-Purpose Bridge on Re-routing Southwestern Region’s Connectivity to Dhaka - Morshed, Md Manjur; Das, Swadhin (Journal of Engineering Science, 2025)
The Padma Multi-purpose Bridge (PMB) is a milestone project of Bangladesh. The PMB connects the southwestern districts with Dhaka and has reduced travel time and distance. The objective of this research is to explore how the traffic from 21 southwestern districts has been rerouted from the previously taken route, Paturia-Aricha. Using Dijkstra's Algorithm and Google API data, the shortest path and quickest path to Dhaka are estimated before and after the opening of the PMB on 26 June, 2022, for 21 districts. The outputs are mapped in GIS. Besides comparing the shortest path and quickest path before and after the PMB, an analysis is made on how some districts prefer the quickest path over the shortest path. Finally, a map shows the influence zone of the PMB on rerouting the traffic from 21 southwestern districts. Journal of Engineering Science 16(1), 2025, 81-92